Pengembangan Instrumen Penilaian Literasi Kelautan untuk Siswa Sekolah Menengah Atas - hindrasti, nur eka kusuma (Jurnal Kiprah, 2018)
ABSTRACTThe preliminary study of students' understanding of the sea, where the sea is an important object in maritime affairs, is very much needed to support the academic curriculum which was initiated by the Indonesian Government. Understanding of the sea internationally has been widely studied in ocean literacy. Studies on marine literacy in Indonesia are still very few, even though Indonesia is the second country with the longest coastline in the world. Ocean literacy instruments need to be developed in advance to conduct a preliminary study of ocean literacy. The purpose of this study was to produce a valid and reliable ocean literacy assessment instrument for high school students. The stages in developing instruments include: designing, testing, determining validity, and determining the reliability of the instrument. The results of the study showed that ocean literacy instruments included a ocean insight test, questionnaire of student's attitude towards the sea, and questionnaire of student's behavior towards the sea. The instruments that have been produced was valid and reliable. Keywords: instrument of ocean literacy ABSTRAKKajian awal mengenai pemahaman siswa terhadap laut, dimana laut adalah objek penting dalam kemaritiman, sangat dibutuhkan untuk mendukung kurikulum kemairitiman yang mulai digagas oleh Pemerintah Indonesia. Pemahaman terhadap laut secara internasional telah banyak dikaji dalam literasi kelautan (ocean literacy). Kajian tentang literasi kelautan di Indonesia masih sangat sedikit, padahal Indonesia adalah negara kedua dengan garis pantai terpanjang sedunia. Instrumen literasi kelautan perlu dikembangkan terlebih dahulu guna melakukan kajian awal mengenai literasi kelautan. Tujuan penelitian ini adalah menghasilkan instrumen penilaian literasi kelautan untuk siswa SMA yang valid dan reliabel. Tahapan dalam pengembangan instrumen mencakup: perancangan, uji coba, penetapan validitas, dan penetapan realibilitas instrumen. Hasil penelitian menunjukkan bahwa instrumen literasi kelautan meliputi tes wawasan kelautan, angket sikap kepedulian siswa terhadap laut, dan angket perilaku siswa terhadap laut. Instrumen yang dihasilkan valid dan reliable.